The Role of Oxidant Stress on AT1 Receptor Expression in Neurons of Rabbits with Heart Failure and in Cultured Neurons - Liu, Dongmei (2008)
We have previously reported that the expression of Angiotensin II (Ang II) type 1 receptors (AT1R) was increased in the rostral ventrolateral medulla (RVLM) of rabbits with chronic heart failure (CHF) and in the RVLM of normal rabbits infused with intracerebroventricular (ICV) Ang II. The present study investigated if oxidant stress plays a role in Ang II induced AT1R up-regulation and its relationship to the transcription factor activator protein 1 (AP1) in CHF rabbits and in the CATHa neuronal cell line. In CATHa cells, Ang II significantly increased AT1R mRNA by 123 ± 11%, P<0.01; c-Jun mRNA by 90 ± 20%, P<0.01; c-fos mRNA by 148 ± 49%, P<0.01; NADPH oxidase activity by 126 ± 43%, P<0.01 versus untreated cells. Tempol and Apocynin reversed the increased expression of AT1R mRNA, c-Jun mRNA, c-fos mRNA, and superoxide production induced by Ang II. We also examined the effect of ICV Tempol on the RVLM of CHF rabbits. Compared to vehicle treated CHF rabbits, Tempol significantly decreased AT1R protein expression (1.6±0.29 vs 0.88±0.16, P<0.05), phosphorylated Jnk protein (0.4 ± 0.05 vs 0.2 ± 0.04, P<0.05), cytosolic phosphorylated c-Jun (0.56 ± 0.1 vs 0.36 ± 0.05, P<0.05), and nuclear phosphorylated c-Jun (0.67±0.1 vs 0.3±0.08, P<0.01). Tempol also significantly decreased the AP-1-DNA binding activity in the RVLM of CHF rabbits compared to the vehicle group (9.14 × 10(3) vs 41.95 × 10(3) grey level P<0.01). These data suggest that Ang II induces AT1R up-regulation at the transcriptional level by induction of oxidant stress and activation of AP1 in both cultured neuronal cells and in intact brain of rabbits. Antioxidant agents may be beneficial in CHF and other states where brain Ang II is elevated by decreasing AT1R expression through the Jnk and AP1 pathway.